PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS DAN PRODUKTIVITAS PADA PERBANKAN SYARIAH DI INDONESIA - Fadri, Zainal; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The research is aimed to provide empirical evidence about the influence of intellectual capital to the financial performance of Sharia Banking in Indonesia. In this research, the intellectual capital is measured using the iB-VAICTM. Meanwhile, the performance of the company in this research has been measured by using the measures of profitability (ROA) and productivity (ATO). This research has been done by using secondary data and the sample collection technique has been carried out by using purposive sampling method. 100 quarterly reports of 5 Sharia Commercial Banks in Indonesia have been selected as samples, and the observation period with 5-year time spans from 2010-2014 has been obtained. The result of the research shows that the first hypothesis is accepted, there is a positive influence between the intellectual capital to the profitability of the Sharia banking. The second hyopthesis is accepted, there is a positive influence between intellectual capital and the productivity. It can be concluded from the result of the research that intellectual capital can give positive influence to the performance of the company.Keywords: Intellectual capital, iB-VAICTM, profitability, productivity, sharia banking.